2016
DOI: 10.1103/physreve.94.013105
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of circular arrangements of vorticity in two dimensions

Abstract: The merger of two like-signed vortices is a well-studied problem, but in a turbulent flow, we may often have more than two like-signed vortices interacting. We study the merger of three or more identical corotating vortices initially arranged on the vertices of a regular polygon. At low to moderate Reynolds numbers, we find an additional stage in the merger process, absent in the merger of two vortices, where an annular vortical structure is formed and is long lived. Vortex merger is slowed down significantly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…In this work 8 it was observed that the sustained vortex pattern preceded with the formation of hole capture and transient hole patterns within the patch vortex. Similar observation was later reported by Swaminathan et al 11 in the incompressible limit. The direct parallel between such an arrangement of fluid vortices and magnetised plasma column under strong axial magnetic field had been exploited in the past 8 .…”
Section: A Physics Aspectssupporting
confidence: 89%
See 1 more Smart Citation
“…In this work 8 it was observed that the sustained vortex pattern preceded with the formation of hole capture and transient hole patterns within the patch vortex. Similar observation was later reported by Swaminathan et al 11 in the incompressible limit. The direct parallel between such an arrangement of fluid vortices and magnetised plasma column under strong axial magnetic field had been exploited in the past 8 .…”
Section: A Physics Aspectssupporting
confidence: 89%
“…Also the results qualitatively match with the recent observation by Swaminathan et al 11 addressed using Fourier pseudo-spectral technique. A detailed and complete description of the merging process is depicted in these 8,11 earlier communications in incompressible limit (M ≡ 0).…”
Section: A Results In Incompressible Limitmentioning
confidence: 99%
“…Similarly, in an N-vortex configuration, when N identical point vortices are placed at the vertices of a regular polygon, we have N fixed points. The behaviour of N vortices started out thus is interesting in itself, and the reader is referred to [30]. In the present article we ask how stable the fixed points are, i.e., up to what Stokes number particles can they attract to themselves.…”
Section: Attracting Fixed Points In Rotating Framesmentioning
confidence: 95%
“…Similar to defect dynamics in the GL equation [30,33,34], each vortex gets attracted to the saddle due to the opposite topological charge; (ii) The two vortices rotate around each other similar to convective merging in NS [31,32]; and (iii) The flexure of the vortex trajectory depends on the Re (see Supplemental Material). Thus a vortex merger event in the two-dimensional ITT equation has ingredients both from the NS and GL equations.…”
Section: (B) and (C)]: (I)mentioning
confidence: 94%
“…On the other hand, for high Re = 2π × 10 4 , vorticity snapshots resemble 2D turbulence. In particular, similar to vortex merger events in 2D [31,32], it is easy to identify a pair of co-rotating vortices undergoing a merger and the surrounding filamentary structure.…”
mentioning
confidence: 99%